Examining the Effects of Job Satisfaction and Motivation on Employee Performance: The Mediating Role of Employee Engagement - Khatri, Shyam Kaji; Bhattarai, Ganesh; Shrestha, Narayan Kumar (NCC Journal, 2025)
This study examines the influence of employee job satisfaction and motivation on their performance, as well as the mediating effect of employee engagement in this relationship. This study used a quantitative methodology using an explanatory research design. Perceptual data were collected from the primary source. Structured questionnaires were utilized to analyze the collected primary data from 384 staff working in government banks in the Kathmandu Valley. Data were analyzed using descriptive statistics, correlation analyses, and structural equation modeling, using SPSS and Smart PLS 4. Reliability and validity assessments of all measures were ensured before data analysis using confirmatory factor analysis. Results of this study showed that employees reported average scores of job satisfaction and motivation, but above-average scores of engagement and performance. There were also positive correlations among all study variables. Moreover, studies found that motivation directly, as well as indirectly through employee engagement, affected employee performance. Job satisfaction influenced performance indirectly through engagement, but not directly. This study offers a number of practical and theoretical contributions endorsing the application of established motivational and engagement models within the Nepalese context.